2019
DOI: 10.1016/j.ijppaw.2019.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Haemocystidium spp., a species complex infecting ancient aquatic turtles of the family Podocnemididae: First report of these parasites in Podocnemis vogli from the Orinoquia

Abstract: The genus Haemocystidium was described in 1904 by Castellani and Willey. However, several studies considered it a synonym of the genera Plasmodium or Haemoproteus. Recently, molecular evidence has shown the existence of a monophyletic group that corresponds to the genus Haemocystidium. Here, we further explore the clade Haemocystidium spp. by studying parasites from Testudines. A total of 193 individuals belonging to six families of Testudines were analyzed. The samples were collected in five localities in Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Thus, to our knowledge, it represented the first report of Haemocystidium in western Europe and the first in the species Tarentola mauritanica . The phylogenetic analysis was similar to those previously described by González et al ( 2019 ) and Austen et al ( 2020 ), with a clade formed by parasites found in chelonians and other clade formed by parasites found in lacertids and snakes. The new lineage ON458135 found from T. mauritanica could be placed together with this second clade with haplotypes from other gecko and a snake species.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, to our knowledge, it represented the first report of Haemocystidium in western Europe and the first in the species Tarentola mauritanica . The phylogenetic analysis was similar to those previously described by González et al ( 2019 ) and Austen et al ( 2020 ), with a clade formed by parasites found in chelonians and other clade formed by parasites found in lacertids and snakes. The new lineage ON458135 found from T. mauritanica could be placed together with this second clade with haplotypes from other gecko and a snake species.…”
Section: Discussionsupporting
confidence: 85%
“…Besides, new molecular markers would improve phylogenetic relationships. The mitochondrial genome has been seen as a good candidate given the evolution rate of the genes encoded there (Escalante et al ., 1998; Pacheco et al ., 2017) as well as their widespread use in other apicomplexa groups of parasites (Bensch et al ., 2000; Martinsen et al ., 2008; Perkins, 2008; Ogedengbe et al ., 2011; Witsenburg et al ., 2012; Borner et al ., 2016; González et al ., 2019 among others). In this regard, recent advances have been achieved for the mitochondrial genome sequencing of Hepatozoon catesbianae and Hepatozoon griseisciuri (Léveillé et al ., 2014, 2020), from which high genetic divergences have been found within the nominal taxa.…”
Section: Discussionmentioning
confidence: 93%
“…During the past decade, many studies have characterized the apicomplexan parasites that infect reptiles of tropical regions of South America (i.e. O'Dwyer et al ., 2013; Pineda-Catalan et al ., 2013; Borges-Nojosa et al ., 2017; Matta et al ., 2018; Úngari et al ., 2018; González et al ., 2019). Despite this, knowledge about Haemogregarines, particularly in Testudines, is still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…3 ). The phylogenies, overall, coincide with those previously reported that included other parasites from reptiles (González et al ., 2019 ; Pacheco et al ., 2020 ; Córdoba et al ., 2021 ). Both phylogenetic hypotheses showed that the parasite found in Turnip-tailed gecko shares a common ancestor with Plasmodium species found in lizards.…”
Section: Resultsmentioning
confidence: 99%